Phase I trial of capecitabine rapidly disintegrating tablets and concomitant radiation therapy in children with newly diagnosed brainstem gliomas and high-grade gliomas - Kilburn, Lindsay B. (Oxford University Press, 2013)
BACKGROUND: We conducted a phase I study to estimate the maximum tolerated dose and describe the dose-limiting toxicities and pharmacokinetics of oral capecitabine rapidly disintegrating tablets given concurrently with radiation therapy to children with newly diagnosed brainstem or high-grade gliomas. METHODS: Children 3–21 y with newly diagnosed intrinsic brainstem or high-grade gliomas were eligible for enrollment. The starting dose was 500 mg/m(2), given twice daily, with subsequent cohorts enrolled at 650 mg/m(2) and 850 mg/m(2) using a 3 + 3 phase I design. Children received capecitabine at the assigned dose daily for 9 wks starting from the first day of radiation therapy (RT). Following a 2-wk break, patients received 3 courses of capecitabine 1250 mg/m(2) twice daily for 14 days followed by a 7-day rest. Pharmacokinetic sampling was performed in consenting patients. Six additional patients with intrinsic brainstem gliomas were enrolled at the maximum tolerated dose to further characterize the pharmacokinetic and toxicity profiles. RESULTS: Twenty-four patients were enrolled. Twenty were fully assessable for toxicity. Dose-limiting toxicities were palmar plantar erythroderma (grades 2 and 3) and elevation of alanine aminotransferase (grades 2 and 3). Systemic exposure to capecitabine and metabolites was similar to or slightly lower than predicted based on adult data. CONCLUSIONS: Capecitabine with concurrent RT was generally well tolerated. The recommended phase II capecitabine dose when given with concurrent RT is 650 mg/m(2), administered twice daily. A phase II study to evaluate the efficacy of this regimen in children with intrinsic brainstem gliomas is in progress (PBTC-030).